2012
DOI: 10.1111/j.2042-3306.2012.00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance and radiographic diagnosis of osseous resorption of the flexor surface of the distal phalanx in the horse

Abstract: Focal radiolucency of the flexor surface of the distal phalanx is a newly recognised radiographic sign associated with pathological changes of the podotrochlear apparatus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…MRI also confirmed the presence of the bilateral focal resorptive lesions and regional sclerosis of the flexor cortex of the distal phalanges that had been suspected radiographically. Similar osseous resorptive lesions have been described previously . It has been hypothesised that these changes result from enthesiopathy of the closely apposed distal insertions of the DSIL and DDFT .…”
Section: Discussionsupporting
confidence: 69%
“…MRI also confirmed the presence of the bilateral focal resorptive lesions and regional sclerosis of the flexor cortex of the distal phalanges that had been suspected radiographically. Similar osseous resorptive lesions have been described previously . It has been hypothesised that these changes result from enthesiopathy of the closely apposed distal insertions of the DSIL and DDFT .…”
Section: Discussionsupporting
confidence: 69%
“…Early results were presented the following year, and showed that a range of pathological processes could be visualised, including lesions of the deep digital flexor tendon (Mair and others 2003). Over the ensuing years, numerous conditions were described, including cortical erosions of the navicular bone (Sherlock and others 2008), collateral desmitis of the distal interphalangeal joint (Dyson and others 2004), flexor surface resorption of the pedal bone (Young and others 2012), and abnormalities of the deep digital flexor tendon (Cillan-Garcia and others 2013, Dyson and others 2003, Schramme, 2011). As with all new imaging modalities, it became apparent that there were important artefacts.…”
mentioning
confidence: 99%
“…Two of these studies were featured in the EVJ supplement. The first concerned use of MRI and radiographs to detect osseous resorption of the flexor surface of the coffin bone . Horses that had radiographs and MRI studies of the foot as part of a lameness examination were included in this retrospective study; 82 studies were included from 65 horses with lameness localised to the foot (17 with bilateral lameness).…”
Section: Diagnostic Imagingmentioning
confidence: 99%